Click Crosslinked Chitosan/Gold Nanocomposite Hydrogels. Issue 11 (1st August 2016) - García‐Astrain, Clara; Hernández, Rebeca; Guaresti, Olatz; Fruk, Ljiljana; Mijangos, Carmen; Eceiza, Arantxa; Gabilondo, Nagore
Abstract : A renewable resource‐based nanocomposite hydrogel is prepared after the click cross‐linking of furan‐modified chitosan with maleimide‐functionalized gold nanoparticles. This synthetic strategy is promising for the cross‐linking of biopolymers with functionalized nanoparticles, resulting in materials with advanced properties. Abstract : Preparation of novel nanocomposite hydrogels opens up new avenues to next generation of biocompatible materials to be used in bioengineering and drug delivery. Toward this goal, chitosan nanocomposite hydrogels using click chemistry inspired cross‐linking are prepared. To enable this, Diels–Alder reaction of furan‐containing chitosan and maleimide‐coated gold nanoparticles is employed. The viscoelastic properties of the obtained nanocomposites as well as the effect of the nanoparticles as cross‐linkers are studied, indicating that they play significant role in hydrogel formation and stability. Nanoparticle‐enriched hydrogels are also found to demonstrate pH‐sensitivity therefore showing their potential for future biosensing applications.